Research on Three-Phase Grid-Connected Control System Based on Current Decoupling - Lang, Baohua; Li, Jichao; Sun, Luyan; Wang, Birong (2022 8th International Conference on Control Science and Systems Engineering (ICCSSE), 2022)
Based on the dq model of the three-phase grid-connected inverter, the first-order and second-order current decoupling closed-loop control algorithms are deduced in detail. The first-order and second-order current decoupling grid-connected control system are simulated and verified by Matlab/Simulink. At the same time, an experimental platform is further built with DSP as the control core for experimental verification. The simulation and experimental results show that the grid-connected control system based on current decoupling works well, the amplitude and phase of the grid-connected current are controllable, and it can transmit energy from the DC side to the grid side with unity power factor.